Size-suppressed dielectrics of Ge nanocrystals : skin-deep quantum entrapment - Goh, Eunice S. M. (2013)
Although the dielectric behavior of nanostructured semiconductors has been intensively investigated, the physics behind observations remains disputed with possible mechanisms such as quantum confinement and dangling bond polarization. Here we show that theoretical reproduction of the measured dielectric suppression of Ge nanocrystals asserts that the dielectric suppression originates from the shorter and stronger bonds at the skin-deep surface, the associated local densification and quantum entrapment of energy. Coordination-imperfection induced local quantum entrapment perturbs the Hamiltonian that determines the band gap and hence, the process of electron polarization consequently.